Antimicrobial Ionic Liquid‐Based Materials for Biomedical Applications. (23rd July 2021) - Nikfarjam, Nasser; Ghomi, Matineh; Agarwal, Tarun; Hassanpour, Mahnaz; Sharifi, Esmaeel; Khorsandi, Danial; Ali Khan, Moonis; Rossi, Filippo; Rossetti, Arianna; Nazarzadeh Zare, Ehsan; Rabiee, Navid; Afshar, Davoud; et al.
Abstract: Excessive and unwarranted administration of antibiotics has invigorated the evolution of multidrug‐resistant microbes. There is, therefore, an urgent need for advanced active compounds. Ionic liquids with short‐lived ion‐pair structures are highly tunable and have diverse applications. Apart from their unique physicochemical features, the newly discovered biological activities of ionic liquids have fascinated biochemists, microbiologists, and medical scientists. In particular, their antimicrobial properties have opened new vistas in overcoming the current challenges associated with combating antibiotic‐resistant pathogens. Discussions regarding ionic liquid derivatives in monomeric and polymeric forms with antimicrobial activities are presented here. The antimicrobial mechanism of ionic liquids and parameters that affect their antimicrobial activities, such as chain length, cation/anion type, cation density, and polymerization, are considered. The potential applications of ionic liquids in the biomedical arena, including regenerative medicine, biosensing, and drug/biomolecule delivery, are presented to stimulate the scientific community to further improve the antimicrobial efficacy of ionic liquids. Abstract : Antimicrobial activities of ionic liquids have fascinated biochemists, microbiologists, and medical scientists. The antimicrobial effect of ionic liquids could be tuned by tailoring their structural features. The antibacterial mechanism and the structure–property relationship of ionic liquids with their bactericidal properties are comprehensively discussed. In addition, cytotoxicity as well as the biomedical applications of ionic liquid derivatives are highlighted.